Cinema negro e cinema negra: a luta por (auto)representação no campo cinematográfico nacional - Gonçalves, Kaludy Teles (2023)
The objective of this work is to present an overview of national black cinema, showing that its emergence is the result of a long struggle by black people in search of the reconstruction of their own image. To do so, we will show how the image of black people, reified by European colonizers, was ratified by national cinema for decades and how black people, in contrast, opened up space in search of self-representation. We will also point out how the emergence of public notices with a racial and gender focus is being decisive for the strengthening of national black cinema, allowing the emergence of new screenwriters, actors, directors, producers and technicians and the consequent construction of a new discourse on black bodies with black people as protagonists of their own stories. We will also talk about the importance of public notices for the strengthening of what I call Black Cinema, made from the perspective of black women as subjects who are not subject. The national black-black cinema is, in fact, an achievement of black people in search of their (re)humanization.